Tindak Pidana Pembunuhan Karena Membela Diri Perspektif Hukum Pidana Islam dan Hukum Pidana Nasional - Dwi Dodik Romadoni Wijaya; Helmi Zaki Mardinasyah (Rechtenstudent, 2022)
The crime of murder is a legal event that is forbidden in Islamic law. In criminal law in Indonesia it is regulated in Article 340 of the Criminal Code. However, there are legal consequences if a person commits a criminal act of forced murder because in self-defense one's efforts are to defend oneself against other people's criminal attacks in order to protect life, honor and property, namely by defending oneself when a person is attacked or deprived of his rights. This research is a library research, the materials and data obtained from the library and various other descriptions that are relevant to the problem of the writing topic. The results of the study are that there are similarities and differences in the terms of forced defense in Islamic criminal law and positive law. The equation for these conditions is the protected object (life, honor and property of oneself and others). The fundamental difference is that it exceeds the permissible defense limit. If in positive law it is permissible to go beyond the limits of forced defense on condition that there must be a cause for great mental disturbance (Article 49 paragraph 2) which is casuistic in nature and determined by a psychiatrist. Whereas the view of Islamic Criminal Law in carrying out acts of defense may not exceed the specified limit, if that happens then the excess must be accounted for by the person who committed the act.